Pengaruh Manajemen Pendidikan Islam dalam Meningkatkan Kapabilitas Manajerial Organisasi - M Goris Hoirul M (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the contribution of Islamic education management in enhancing organizational effectiveness through the application of sharia-based values. Using a qualitative approach and content analysis method, this research explores the benefits, challenges, and implementation strategies of Islamic educational management through a systematic literature review. The findings indicate that Islamic education management plays a key role in efficiently managing educational resources, grounded in the Qur’an, the Sunnah, and national regulations. Core principles such as efficiency, ethics, and da'wah mission are essential in its practice. Furthermore, this management contributes to strengthening the social and spiritual capital of educational institutions. These results are expected to provide both theoretical and practical contributions to the development of Islamic education institutions that are relevant and adaptable to current dynamics.